Strategies and Foundational Elements Necessary for the Integrated Development of China’s Sport Industry and Pension Industry - Zhang, Jinghao; Kwanmuangvanich, Parinya (Journal of Roi Kaensarn Academi, 2024)
Promoting the integration of the sports industry and the senior care industry is an important hand in fostering new forms of sports consumption in China. Literature research, expert interviews and quantitative analysis methods are used to reveal the economic logic of the integration of China’s sports industry and pension industry in the new era, and to analyze the development potential of the integration of the two industries through the degree of coupling coordination and grey prediction. It is found that the integration of the two industries is an integrated innovation process in which senior sports market players actively explore new forms of senior sports and recreational consumption under the rational constraints of the growth of the sports industry and the endogenous incentives of the growth of the senior care industry and the goal of promoting the overall improvement of consumer welfare and producer surplus; the degree of coordination of the coupling between the sports industry and the senior care industry is increasing year by year, but the overall level of equilibrium is not yet reached, and the development opportunities and challenges for the sports industry and the senior care industry in China in the new era have been analyzed by means of interviews with experts and quantitative analysis. The development opportunities and challenges of the integration of the two industries co-exist; the future consumption space of China’s senior sports market will continue to expand along with the growth of per capita disposable income of the urban elderly, but the overall trend of growth is slowing down, and the development of the integration of the two industries is expected to be good and the task is still arduous. Based on this, we put forward concrete suggestions such as focusing on stimulating the vitality of the main players in the senior sports market, steadily increasing the ability of the elderly to pay for sports consumption, and pragmatically carrying out national education on population aging embedded in the national fitness program.